Plant‐mycorrhizal interactions mediate plant community coexistence by altering resource demand. Issue 1 (January 2017) - Jiang, Jiang; Moore, Jessica A. M.; Priyadarshi, Anupam; Classen, Aimée T.
Abstract: As the diversity of plants increases in an ecosystem, so does resource competition for soil nutrients, a process that mycorrhizal fungi can mediate. The influence of mycorrhizal fungi on plant biodiversity likely depends on the strength of the symbiosis between the plant and fungi, the differential plant growth responses to mycorrhizal inoculation, and the transfer rate of nutrients from the fungus to plant. However, our current understanding of how nutrient‐plant‐mycorrhizal interactions influence plant coexistence is conceptual and thus lacks a unified quantitative framework. To quantify the conditions of plant coexistence mediated by mycorrhizal fungi, we developed a mechanistic resource competition model that explicitly included plant‐mycorrhizal symbioses. We found that plant‐mycorrhizal interactions shape plant coexistence patterns by creating a tradeoff in resource competition. Especially, a tradeoff in resource competition was caused by differential payback in the carbon resources that plants invested in the fungal symbiosis and/or by the stoichiometric constraints on plants that required additional, less‐beneficial, resources to sustain growth. Our results suggested that resource availability and the variation in plant‐mycorrhizal interactions act in concert to drive plant coexistence patterns. Applying our framework, future empirical studies should investigate plant‐mycorrhizal interactions under multiple levels of resource availability.